Who Expressed What Emotion? Men Grab Anger, Women Grab Happiness - Neel, Rebecca (2012)
When anger or happiness flashes on a face in the crowd, do we misperceive that emotion as belonging to someone else? Two studies found that misperception of apparent emotional expressions – “illusory conjunctions” – depended on the gender of the target: male faces tended to “grab” anger from neighboring faces, and female faces tended to grab happiness. Importantly, the evidence did not suggest that this effect was due to the general tendency to misperceive male or female faces as angry or happy, but instead indicated a more subtle interaction of expectations and early visual processes. This suggests a novel aspect of affordance-management in human perception, whereby cues to threat, when they appear, are attributed to those with the greatest capability of doing harm, whereas cues to friendship are attributed to those with the greatest likelihood of providing affiliation opportunities.